2021
DOI: 10.18203/2320-1770.ijrcog20211104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vitamin D (25OHD) status between fertile and infertile men

Abstract: Background: Vitamin D (25OHD) deficiency has become a modern-day epidemic, being the most common nutritional deficiency worldwide. Many infertile men are experiencing low total sperm count or different semen abnormalities. The aim of this study was to compare serum vitamin D (25OHD) status among fertile and infertile men.Methods: This was an observational (cross sectional comparative) study and was conducted in the Department of Reproductive Endocrinology and Infertility, BSMMU, Dhaka, Bangladesh during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Regarding this indicator, our results are in agreement with the results of other authors who reported a significant decrease in total 25OHD levels in men with abnormal spermogram compared to men with normozoospermia (Holzer et al, 2022; Islam et al, 2022). A few studies did not find a significant difference in the total 25OHD levels between fertile and infertile men (Nasreen et al, 2021).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Regarding this indicator, our results are in agreement with the results of other authors who reported a significant decrease in total 25OHD levels in men with abnormal spermogram compared to men with normozoospermia (Holzer et al, 2022; Islam et al, 2022). A few studies did not find a significant difference in the total 25OHD levels between fertile and infertile men (Nasreen et al, 2021).…”
Section: Discussionsupporting
confidence: 48%
“…Studies about the effect of the free and bioavailable 25OHD A few studies did not find a significant difference in the total 25OHD levels between fertile and infertile men (Nasreen et al, 2021).…”
Section: F I G U R E 1 Comparison Of Gene Expression Levels Of Cyp27b1mentioning
confidence: 99%
“…Data obtained show that vitamin D level defines ejaculate amount and quality in men [44,45] (including sperm cells motility and their morphology [46,47]), and ripening of spermatozoon. The correlation between low concentration of vitamin D and increased quantity of motile and morphologically normal sperms has been determined.…”
Section: оглядиmentioning
confidence: 99%
“…Poor serum 25-hydroxyvitamin D concentrations (25(OH)D) have been detected among young infants as well as pregnant women in Bangladesh, advised to have Vit D supplementation 6 . In Bangladesh, 86% of people have hypovitaminosis D; 61.4% have a deficiency and 24.1% have insufficiency 7 . Symptoms and signs of Vit-D deficiencies are fatigue, bone pain, muscle weakness, joint pain, etc.…”
Section: Introductionmentioning
confidence: 99%